Menentukan Topik Skripsi Mahasiswa Dengan Menggunakan Relasi Fuzzy Intuisionistik - Raden Sulaiman; Rudianto Artiono; Budi Rahajeng (Universitas PGRI Palembang, 2022)
One of the problems that often occurs isÂ the students cannot complete the thesis as expected. One of the factors that always occurs is that the students choose or determine the topic of their thesis that is not in accordance with their competence. He is more likely to choose supervisor.Â This article is the result of research that aims to determine the suitability of a student's thesis topic according to their academic competence. The research was conducted on Unesa Mathematics students who are at the fourth year. The number of subjects are 35 students who were at the beginning of semester 7 and at that time were taking a mathematics seminar course. Seminar courses are the beginning of the preparation of their thesis. The method used is a modification of the